El empleo de metodologías de código abierto para las investigaciones costeras: comparativa de las técnicas de detección de cambios - Alejandro Gómez Pazo (Boletín de la Asociación de Geógrafos Españoles)
Coastal studies have a great relevance historically. This increase in the last with the new technologies and the possible global change impact. In this context, open-source tools represent a key element in these investigations. The present project analyzes the advantages and problems of open-source tools for estimate coastal variations and volumetric changes. For this purpose, a small sector of the Galician coast was used as an example. The open-source approaches have produced similar results to those obtained with proprietary software (ratios ≥ 0.97). In some cases, these methods improve processing times and allowing to users better possibilities for customization and decision-making.